A NOVEL FRAMEWORK FOR SECURE PASSWORD AUTHENTICATION USING ENCRYPTED NEGATIVE PASSWORDS (International Journal of Food and Nutritional Sciences, 2022)
This paper presents a novel secure password authentication framework that utilizes an encrypted negative password mechanism to enhance security and mitigate common vulnerabilities associated with traditional password systems. With the increasing prevalence of cyber threats and data breaches, ensuring robust authentication methods has become imperative. Our proposed framework introduces a unique approach where negative passwords—representing prohibited or blacklisted passwords—are encrypted and stored securely. This technique not only strengthens the password management process by preventing users from selecting weak or easily guessable passwords but also complicates potential attacks by obscuring the password database. We implement a combination of cryptographic algorithms to ensure the integrity and confidentiality of the stored passwords, alongside a user-friendly interface that facilitates seamless authentication. Experimental results demonstrate that our framework significantly improves resistance to various attacks, such as brute force and dictionary attacks, while maintaining user convenience. By addressing the fundamental issues of password security, this framework offers a comprehensive solution for secure user authentication in both personal and enterprise environments, paving the way for more resilient cybersecurity practices.